IMPLEMENTASI PROGRAM PENINGKATAN KEPATUHAN PENGGUNAAN APD SEBAGAI UPAYA PENCEGAHAN PENYAKIT AKIBAT KERJA PADA PEKERJA ARANG DI KOTA BATAM - Noviyanti; Leni Utami; Ujang Amir; Raja Desti Rahma Pratiwi; Rifdah Wafiyana; Cut Putri Afsyarina Plangi Azza; Sherly Cahya Asyura; Noviyanti Noviyanti (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Abstract: Occupational Safety and Health (OHS) is a crucial aspect in various industrial sectors to minimize the risk of Occupational Diseases (OCD). The traditional charcoal making industry in Batam City is an informal sector with high exposure to hazards, such as carbon dust (particulates), toxic gases, and extreme heat radiation. However, worker compliance in using Personal Protective Equipment (PPE) is still very low. Problem: Low compliance is triggered by physical discomfort due to high furnace temperatures, limited capital for informal sector businesses, and minimal worker knowledge regarding the latency of long-term PAK impacts such as anthracosis (black lung disease) and impaired lung function. Method: This Community Service (PKM) activity uses a descriptive qualitative method with a survey approach. The subjects of the activity were 30 charcoal workers in Batam City who were given interventions in the form of interactive counseling, OHS hazard education, simulation of the use of standard PPE (such as N95 respirators, safety glasses, aprons, and gloves), and health checks. Evaluation of the program's success was measured using pre-test and post-test instruments. Results: The evaluation results showed a significant increase in understanding and compliance after the program was implemented. The level of compliance score for PPE use jumped from 10% to 60% (up 50 percentage points), understanding of PAK risks increased from 3.7% to 60% (up 56.3 percentage points), and understanding regarding the type of PPE used increased from 10% to 80% (up 70 percentage points). Conclusion: This PKM program based on a participatory and educational approach has proven effective in increasing awareness, knowledge of latent hazards, and compliance of informal charcoal workers in implementing personal protective equipment standards to prevent the risk of occupational diseases.